2022
DOI: 10.3846/bm.2022.810
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Firm Size and Enterprise Risk Management Level

Abstract: The paper aims to investigate if firm size plays a role as a driver for the ERM method and as an ERM de-terminant. A comprehensive literature review (conducted 2010–2021) and primary data (SMEs in Czech Republic, research conducted in 2021) were applied. Latent class analysis and contingency tables were employed. The results show that firm size predicts the adequate ERM method and has positive effects on the ERM level. The contribution is in identifying significant differences between micro- and medium-sized e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…& Muthuveloo, R. (2015), who showed that firm size is positively related to enterprises' risk management adoption. (Syrová, 2022) (Rujiin & Sukirman, 2019) (Iswajuni, Arina, and Soegeng, 2018) (Gatzert & Martin,2015) (Li, et al, 2014) (Shaleh &Kurniasih, 2021) (Hafizuddin-Syah,2015) (Muslih,2019) (Yegon, Mouni & Wanjau, 2014) (Naseem, et al, 2019) Sithipolvanichgul, (2016 has confirmed, that firm size, market uncertainty, and gross domestic product Sectoral products seem to determine the degree of success of ERM implementations. The success rate of ERM implementation increases as the company gets bigger and its GDP increases.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…& Muthuveloo, R. (2015), who showed that firm size is positively related to enterprises' risk management adoption. (Syrová, 2022) (Rujiin & Sukirman, 2019) (Iswajuni, Arina, and Soegeng, 2018) (Gatzert & Martin,2015) (Li, et al, 2014) (Shaleh &Kurniasih, 2021) (Hafizuddin-Syah,2015) (Muslih,2019) (Yegon, Mouni & Wanjau, 2014) (Naseem, et al, 2019) Sithipolvanichgul, (2016 has confirmed, that firm size, market uncertainty, and gross domestic product Sectoral products seem to determine the degree of success of ERM implementations. The success rate of ERM implementation increases as the company gets bigger and its GDP increases.…”
Section: Discussionmentioning
confidence: 95%
“…The positive effect may be that as the business size increases, it becomes necessary to manage the business through formal procedures and internal guidelines. Small businesses lack reliable resources and mechanisms to support their risk management activities (Syrová, 2022) (Rujiin & Sukirman, 2019). Large firms may diversify their operations to mitigate unsystematic risks.…”
Section: Firm Size and The Enterprise's Risk Management Practicesmentioning
confidence: 99%